Choleric Cemeteries in the Landscape of the Northern Part of the Polish Jurassic Highland - Aleksandra Krupa-Ławrynowicz; Olgierd Ławrynowicz (Fasciculi Archaeologiae Historicae, 2021)
This paper presents the results of ethnographic and archaeological research into potential places of epidemic burial (choleric cemeteries) in two communes in the northern part of the Polish Jurassic Highland, Janów and Mstów. In their descriptions and analysis, ethnographic sources (local memory, accounts provided by inhabitants) and archaeological sources (non-destructive prospecting, probing research) were applied. Apart from presentation of field material, the aim of the paper is to indicate the potential of a combined ethnoarchaeological method applied in research to the contemporary past and to the landscape understood as cultural heritage.